Riba dalam Perspektif Tasawuf - Suharyono Suharyono; Lenda Surepi (IAIN Bengkulu, 2022)
There are quite a lot of writings or studies on usury, in this case the author will discuss the focus of the study of usury from the perspective of Sufism. The method used is the literature or library study method. The conclusion of this scientific paper is that Islam forbids the concept of usury especially there are Muslims who practice the teachings of Sufism who strongly oppose and leave something that is clearly prohibited in Islam.